Application Of Security System Of Motorcycle Used Fingerprint Optical Sensor And Vibration Sensor With Fuzzy Logic Based On Arduino Uno R3 - Mhd Furqan; Muhammad Ikhsan; Abdul Halim Hasugian; Muhammad Ridzki Hasibuan (INFOKUM, 2021)
The Increasing case of motorcycle theft in North Sumatera and lack of human control of safety locks is an important factor for every motorcycle owner to ad dual security system. The research aimed to add double protection of the motorcycle by utilizing the advantages of the Fingerprint sensor plus a vibrating sensor SW-420 and IR Proximity sensor which is controlled by a microcontroller with fuzzy logic as process logic. The fuzzy logic used to produce the output of motorcycle condition which is silent, shifted by early is the alarm if there are the other individuals who try ignite or move the motorcycle position. The microcontroller is used to control relay based on verification results from Fingerprint optical sensor FPM10A module as well as do the process of fuzzy logic at vibrating sensor SW-420 module and IR Proximity sensor then it will produce the alarm output is sound. These protection system tools can increase the safety of the motorcycle owner.